Metacognitive Blindness in Mathematics Problem-Solving - Surya Sari Faradiba; Alifiani Alifiani (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
Metacognitive blindness is usually synonymous with low math ability. However, this study reveals the opposite. Metacognitive blindness can also be experienced by students with good learning achievement. This research was conducted on students majoring in Mathematics Education who have the best academic achievement in their class. The data collected is in the form of words obtained through interviews after solving math problems. The results of the qualitative analysis show that subjects who are students with good academic performance can experience anomalous results during the problem-solving process, which is a condition in which the subject feels that the math problem at hand contains errors. The error in question is, the subject stutters the squares on the chessboard that are not the same size, but in reality they are not.